A Self‐Powered Implantable Drug‐Delivery System Using Biokinetic Energy. Issue 11 (9th January 2017) - Song, Peiyi; Kuang, Shuangyang; Panwar, Nishtha; Yang, Guang; Tng, Danny Jian Hang; Tjin, Swee Chuan; Ng, Wun Jern; Majid, Maszenan Bin Abdul; Zhu, Guang; Yong, Ken‐Tye; Wang, Zhong Lin
Abstract : The first triboelectric‐nanogenerator (TENG)‐based self‐powered implantable drug‐delivery system is presented. Pumping flow rates from 5.3 to 40 µL min −1 under different rotating speeds of the TENG are realized. The implantable drug‐delivery system can be powered with a TENG device rotated by human hand motion. Ex vivo trans‐sclera drug delivery in porcine eyes is demonstrated by utilizing the biokinetic energies of human hands.